A Review on Anti-Breast Cancer Activity of Selected Medicinal Plants (Asian Journal of Pharmaceutics (AJP), 2024)
To review and identify medicinal plants and bioactive substances with potential anti-breast cancer activity andprovide a complete overview for future research. A comprehensive analysis of all scientific studies, phytochemicalscreening, ethnobotanical surveys, plant medicinal applications, and anti-breast cancer activities of medicinalplants was conducted. These data were gathered by searching for relevant articles in databases such as PubMed,Scopus, Google Scholar, and Web of Science. Relevant studies included those published in peer-reviewed journalsand reports from respective conservation agencies. The reviewed medicinal plants and their bioactive componentsdemonstrated promising anti-breast cancer activities, including antiproliferative, apoptotic, anti-angiogenic, andantioxidant activities. This study emphasizes the potential of medicinal plants and their bioactive chemicals for thetreatment of breast cancer. This is a significant resource for future research and the development of effective plantbasedmedicines. Herbal medications are promising alternatives to traditional chemotherapy, with fewer sideeffects and greater tolerability. Further research is required to fully understand the anti-breast cancer capabilitiesof these medicinal plants and their bioactive components.